2021
DOI: 10.51542/ijscia.v2i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Applications of Nanomaterials for Ophthalmic Applications

Abstract: The development of theranostic applications of nanomaterials has presented researchers with a new form of diagnosing and treating diseases, such as cancer, Diabetic Retinopathy, and Age-Related Macular Degeneration. Theranostic have allowed for a bridge between conventional medicine and personalized medicine with the use of nanomaterials. The applications of nanomaterials within medicine (nanomedicine) have changed the diagnosis, monitoring, control, treatment, and prevention of diseases. The effects of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…In fact, some eye diseases require a prompt diagnosis in order to contain possible damages related to the ongoing pathways involved. Age-related macular degeneration (AMD) is the main cause of vision loss for over-65-year-olds [ 37 ]; this pathology has often been analyzed to improve diagnostic techniques since it has several predisposing factors, and early detection is crucial to avoid degeneration toward blindness [ 140 ]. AMD has an unclear etiology, although oxidative stress is considered one of the main risk factors [ 141 ]; as a matter of fact, clinical studies demonstrated the importance of supplementation with antioxidants in order to slow down the progression of AMD [ 142 , 143 ].…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, some eye diseases require a prompt diagnosis in order to contain possible damages related to the ongoing pathways involved. Age-related macular degeneration (AMD) is the main cause of vision loss for over-65-year-olds [ 37 ]; this pathology has often been analyzed to improve diagnostic techniques since it has several predisposing factors, and early detection is crucial to avoid degeneration toward blindness [ 140 ]. AMD has an unclear etiology, although oxidative stress is considered one of the main risk factors [ 141 ]; as a matter of fact, clinical studies demonstrated the importance of supplementation with antioxidants in order to slow down the progression of AMD [ 142 , 143 ].…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%
“…The development of these applications has given researchers a new way of diagnosing and treating diseases such as cancer, diabetic retinopathy and age-related macular degeneration [ 37 , 155 ]. Among the major chronic eye diseases, diabetic retinopathy is the most prevalent.…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%
See 1 more Smart Citation